Best Practice Review: Enhancing the Quality of Shariah Economist Scholars - Mubarak, Jaih; Mahfudz, Shaifurrokhman (Universitas Muhammadiyah Surakarta, 2024)
This research aims to overcome important gaps in the development of Islamic economic scholars' human resources (HR), including limited understanding of Fiqh Muamalah, unclear profiles of graduates, and lack of linkages with the Islamic industry. The implications of current conditions include the quality of Islamic products and services, the sustainability of industry growth, and the relevance of graduates. This research will provide guidance and best practice strategies to connect graduate profiles with the dynamics of the sharia industry, strengthen the human resources of sharia economic scholars, and support the development of a better sharia industry.